Tocotrienol decreases ß-amyloid mediated toxicity in Caenorhabditis elegans model of Alzheimer's disease - Chee wah yuen; Mardani Abdul Halim; Vikneswaran murugaiyah; Nazalan Najimudin; Ghows Azzam (Researchgate, 2020)
Alzheimer’s disease (AD) is a neurological disease caused by the accumulation of extracellular senile plaques consisting of β-amyloid peptide (Aβ) in the brain. A transgenic Caenorhabditis elegans which demonstrated paralysis due to the expression of human beta amyloid Aβ42 gene was used to study the anti-paralysis effect of mixed tocotrienols. The content of the mixed tocotrienols were 12.1% α-, 2.7% β-, 18.6% γ-, and 8.1% δ-tocotrienols. Mixed tocotrienols significantly delayed the Aβ-induced paralysis in the transgenic nematode and exhibited anti-oxidant properties towards Aβ-generated oxidative stress. The mixture also presented potent inhibitory activities against Aβ aggregation with an IC50 value of 600 ng/ml. It is concluded that mixed tocotrienols could potentially serve as a new therapeutic candidate for AD.